Utilitarismo, deontologia kantiana e animais: análise e avaliação críticas - Gonçalves, Sara Fernandes (2015)
The relation between people and animals has been examined over time, with the exclusion of animals from our moral concern. Animals are thus exploited daily and used as resources for human needs: testing, research, clothing, entertainment, hunting, as well as providing useful by- products to humans. This study aims to analyze and evaluate the status of animals from a moral point of view and from theories that hold that animals have rights and interests to be considered. The study begins with considerations of ethics and their universalist character. The universality of moral judgments means that they apply to all beings in similar circumstances. In this sense, the theory, especially according to the utilitarian version of Peter Singer, evaluates the application of the principle of equal consideration for all beings with similar interests, which includes animals and their feelings. Considering that animals have morally significant interests, together with the universalist character of Ethics, we cannot ignore the preferences of the animals in our relationship with them. For Singer, conduct is morally correct if it meets the most impartial preferences of individuals affected by the action. This leads us to conclude that sentient animals should be treated as we should treat human beings with similar interests. Using Kantian theory, in terms of rights, Tom Regan, evaluates that sentient animals are equal to humans, with a complex mental life, they are subjects-of-a-life, and. As such, like us, they have inherent value. This obliges us to treat them with respect. A similar theory, elaborated by Gary Francione, attacks the legal status of animals as mere human property, stating that they are not things but persons, and as such protection should be assured of their interests, just as we do with human beings. Regan and Francione thus profess a kind of deontological ethics (based on rights and obligations as barriers to the pursuit of the collective welfare), and believe strongly that animals have moral rights just as humans. This is unlike Peter Singer, whose theory is consequentialist in nature (based on impartial calculations of the overall best consequences for all affected). He believes that there are no individual moral rights above the general utility. These theories have similar, as well as opposing, implications when applied. The present research compares the theories and evaluates the plausibility of putting them into practice. The abolition of the use of animals, one of the implications of ethical theory promoted by some activists, requires equal consideration of interests and the fair treatment of all individuals as equals. Two practical aspects that receive most attention are the ethics of eating meat and the ethics of animal experimentation.